2013
DOI: 10.1248/cpb.c13-00516
|View full text |Cite
|
Sign up to set email alerts
|

Two New Pyrrolidine Alkaloids, Codonopsinol C and Codonopiloside A, Isolated from <i>Codonopsis pilosula</i>

Abstract: A new pyrrolidine alkaloid codonopsinol C (1), and pyrrolidine alkaloidal glycoside, codonopiloside A (2), were isolated from the roots of Codonopsis pilosula, along with four known pyrrolidine alkaloids, codonopsinol A (3), codonopsinol B (4), codonopyrrolidium B (5), and radicamine A (6). The structures of the new compounds were established by acid hydrolysis and spectroscopic methods. We describe those structures in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 8 publications
(11 reference statements)
1
24
0
Order By: Relevance
“…Previous studies showed that extracts of the C. pilosula roots exhibited pharmacological effects in protecting against peptic ulceration and promoting its healing, enhancing immunity, and improving learning and memory behavior, as well as inhibiting inducible NO synthase and protein oxidation and attenuating the cardiac-impaired insulin-like growth factor II receptor pathway 2 , 3 , 4 , 5 , 6 . Meanwhile, different types of chemical constituents were isolated from the extracts, such as phytosteroids, sesquiterpenes, triterpenes, alkaloids, alkyl alcohol glycosides, phenylpropanoid glycosides, polyacetylene glycosides and polysaccharides 7 , 8 , 9 , 10 , 11 , 12 , of which only polysaccharides were biologically evaluated 13 , 14 , 15 , 16 , 17 . As part of a program to systematically study the chemical diversity of traditional Chinese medicines and their biological effects, focusing on minor small molecules 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , an aqueous decoction of the C. pilosula roots was investigated since a variety of formulations containing “Dang shen” are practically used by decocting with water.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that extracts of the C. pilosula roots exhibited pharmacological effects in protecting against peptic ulceration and promoting its healing, enhancing immunity, and improving learning and memory behavior, as well as inhibiting inducible NO synthase and protein oxidation and attenuating the cardiac-impaired insulin-like growth factor II receptor pathway 2 , 3 , 4 , 5 , 6 . Meanwhile, different types of chemical constituents were isolated from the extracts, such as phytosteroids, sesquiterpenes, triterpenes, alkaloids, alkyl alcohol glycosides, phenylpropanoid glycosides, polyacetylene glycosides and polysaccharides 7 , 8 , 9 , 10 , 11 , 12 , of which only polysaccharides were biologically evaluated 13 , 14 , 15 , 16 , 17 . As part of a program to systematically study the chemical diversity of traditional Chinese medicines and their biological effects, focusing on minor small molecules 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , an aqueous decoction of the C. pilosula roots was investigated since a variety of formulations containing “Dang shen” are practically used by decocting with water.…”
Section: Introductionmentioning
confidence: 99%
“…modesta Roots [ 12 ] C. tangshen Roots [ 13 ] 6 Codonopyrrolidium B C. pilosula Roots [ 14 ] C. pilosula var. modesta Roots [ 12 ] C. tangshen Roots [ 13 ] 7 Codonopsinol A C. pilosula Roots [ 11 ] 8 Codonopsinol B C. pilosula Roots [ 11 ] 9 Codonopsinol C C. pilosula Roots [ 11 ] 10 Codonopiloside A C. pilosula Roots [ 11 ] 11 Codotubulosine B C. tubulosa Roots [ 15 ] 12 n -9-Formyl harman C. lanceolata Roots [ 16 ] 13 Norharman C. lanceolata Roots [ ...…”
Section: Chemical Constituents Of Genus Codonopsismentioning
confidence: 99%
“…modesta [ 12 , 14 ]. In addition, the pyrrolidine alkaloids codonopsinols A ( 7 ), B ( 8 ), C ( 9 ) and the glycoside, codonopiloside A ( 10 ) were obtained from the roots of C. pilosula [ 11 ]. Codotubulosine B ( 11 ) was found in the roots of C. tubulosa [ 15 ].…”
Section: Alkaloidsmentioning
confidence: 99%
“…6,7 The phytochemical studies of this genus have shown presence of major phytocomponents like alkaloids, phenylpropanoids, organic acid, triterpenoids, polyacetylene and polysaccharides. [8][9][10] Codonopsis clematidea is one of the species of Codonopsis, reported in Ladakh region which is used in traditional medicinal systems of this region (Amchi medicinal systems). This plant has been found to produce a pungent smell with bell-shaped flowers.…”
Section: Introductionmentioning
confidence: 99%